A Ubiquitin-binding domain that binds a structural fold distinct from that of Ubiquitin - Lim, M; Newman, J; Williams, H; Masino, L; Aitkenhead, H; Gravard, A; Gileadi, O; Svejstrup, J (Elsevier, 2019)
Ubiquitylation, the posttranslational linkage of ubiquitin moieties to lysines in target proteins, helps regulate a myriad of biological processes. Ubiquitin, and sometimes ubiquitin-homology domains, are recognized by ubiquitin-binding domains, including CUE domains. CUE domains are thus generally thought to function by mediating interactions with ubiquitylated proteins. The chromatin remodeler, SMARCAD1, interacts with KAP1, a transcriptional corepressor. The SMARCAD1-KAP1 interaction is direct and involves the first SMARCAD1 CUE domain (CUE1) and the RBCC domain of KAP1. Here, we present a structural model of the KAP1 RBCC-SMARCAD1 CUE1 complex based on X-ray crystallography. Remarkably, CUE1, a canonical CUE domain, recognizes a cluster of exposed hydrophobic and surrounding charged/amphipathic residues on KAP1, which are presented in the context of a coiled-coil domain, not in a structure resembling ubiquitin. Together, these data suggest that CUE domains may have a wider function than simply recognizing ubiquitin and the ubiquitin-fold.